Measuring the Level of Employee Job Satisfaction and Identify Factors Influencing Job Satisfaction Using Job Descriptive Index Questionnaire: case Study in PT Heartwarmers main Office - Pratiwi, Friska Putri; Welly, John (Journal of Business and Management, 2014)
PT Heartwarmer is the pioneer of woman accessories who has been running for more than15 years. In 2014, they have 300 employees and 60 stores around Indonesia. The main theme of this research are to measure the level of employee job satisfaction and to identify which factor influencing most towards job satisfaction in the main office of PT Heartwarmer. it also investigate the relationship between job satisfactionâ€™s factor with overall job satisfaction. It focuses on the five facets based on Herzberg two factor theory and measured by Job Descriptive Index questionnaire which are job, pay, promotion opportunity, supervision and coworker. This research is using descriptive statistic and SPSS 19 to analyzed collected data. The result of this research shows that the level satisfaction of employee in the main office of PT Heartwarmer is neutral. Eventough the multivariat regression analysis has e Â is selected for the research because they are currently undergoing continued to growth while the employee could perform and work well. In order to gain advantage and adapt to competitive environment